2014
DOI: 10.1152/ajpgi.00082.2014
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cells of Cajal mediate nitrergic inhibitory neurotransmission in the murine gastrointestinal tract

Abstract: (ICC), and fibroblast-like cells. Up to date, the interplay between neurons and these cells to initiate a nitrergic inhibitory junction potential (IJP) is unclear. Here, we investigate the origin of the nitrergic IJP in murine fundus and colon. IJPs were determined in fundus and colon SMC of mice lacking NO-GC globally (GCKO) and specifically in SMC (SM-GCKO), ICC (ICC-GCKO), and both SMC/ICC (SM/ICC-GCKO). Nitrergic IJP was abolished in ICC-GCKO fundus and reduced in SM-GCKO fundus. In the colon, the amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 39 publications
2
70
0
Order By: Relevance
“…␤ 1 -trafficking, changes in post translational modification). NO is involved in rapid anterograde trafficking of ␤ 1 -subunit from the endosomes to the cell membrane and helps ␤ 1 -subunit to associate with BK ␣-subunit elevating channel Ca 2ϩ sensitivity in myocytes (36). Therefore, trafficking of the ␤ 1 -subunit to the cell membrane may be impaired in HFD mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…␤ 1 -trafficking, changes in post translational modification). NO is involved in rapid anterograde trafficking of ␤ 1 -subunit from the endosomes to the cell membrane and helps ␤ 1 -subunit to associate with BK ␣-subunit elevating channel Ca 2ϩ sensitivity in myocytes (36). Therefore, trafficking of the ␤ 1 -subunit to the cell membrane may be impaired in HFD mice.…”
Section: Discussionmentioning
confidence: 99%
“…BK ␤ 1 -subunit downregulation contributes to hypertension (67), heart failure (62), urinary bladder over activity (43) and impaired colonic motility (19). Although obesity (28), oxidative stress (52,56), and NO availability (36) all modulate the function or expression of ␤ 1 -subunits in vascular SMCs, it is unclear if similar modulation occurs in GI SMCs.…”
mentioning
confidence: 99%
“…In this study it was shown that NO-GC was expressed in several cell types including ICC and SMCs. To determine the role of NO-GC in each cell type, Lies et al 221 …”
mentioning
confidence: 99%
“…The development of conditional knockouts deficient in receptors/pathways for some cell subtypes opens up multiple research possibilities in this setting. An example is the above-mentioned study by Lies et al (73), carried out in a mouse deficient for sGC (the receptor mediating NO relaxation) only in ICCs or only in smooth muscle cells. Their findings showed that loss of this receptor in ICCs greatly reduced neurotransmission (hyperpolarization or IJPs), but a functional portion remained, which suggests that both hypotheses might be compatible (partly direct and partly indirect).…”
Section: Direct Vs Indirect Actionmentioning
confidence: 99%